Concurrent validity of the Professional Fulfillment Index in a sample of pharmacy residents and preceptors. - Gustafson, Kyle A; Bates, Brittany; Cline, Kristine M; Gothard, M David (American Journal of Health-System Pharmacy, 2023)
Purpose The purpose of this study was to validate the Stanford Professional Fulfillment Index (PFI) for assessment of burnout and professional fulfillment in a study population of pharmacy residents and residency preceptors. Summary The historical gold standard for assessing professional burnout is the Maslach Burnout Inventory (MBI); there is no established standard for professional fulfillment. The PFI is a 16-question assessment that has previously been validated in medical residents and practicing physicians. In this study, surveys including both PFI and MBI items were sent to active pharmacy residents and residency preceptors. To determine concurrent validity, domains of the PFI were compared to the closest related MBI domain as well as composite burnout rates measured in each portion of the survey. A total of 142 preceptors and 68 residents completed both the PFI and a version of the MBI previously validated in physicians. In assessing indicators of pharmacist burnout and fulfillment, data captured by domains of the PFI closely correlated with data captured by corresponding domains of the MBI (Pearson correlations of 0.683-0.822), with high internal consistency (Cronbach α of 0.866-0.903). Conclusion The PFI is a valid method of assessing burnout in both pharmacy residents and residency preceptors. Additionally, the PFI contributes a reliable system of assessing professional fulfillment while also being highly accessible for both research and residency program monitoring applications.